Pengaruh Media Pembelajaran Berbasis TPACK terhadap Kemampuan Menulis Teks Anekdot Siswa Kelas X SMA Negeri 1 Malingping - Novianti, Anih (Universitas Mathla'ul Anwar Banten, 2024)
This research aims to determine: 1) the ability to write anecdotal texts for class X SMA Negeri 1 Malingping students using learning media in the form of the Canva application; 2) the ability to write anecdotal texts for class X SMA Negeri 1 Malingping students using learning media in the form of the PixelLab application. This research was conducted using the experimental method and class X students for the 2023/2024 academic year as the population. The sample technique uses random sampling. The samples taken were class X E-6 and class X E-10 with a total of 74 students. The results of post-test calculations using the Canva application obtained Mean (????̅) = 81.24, Median (Me) = 80.00, Variance = 76,088 and standard deviation = 8,723. Meanwhile for the control class post-test scores used PixelLab application, namely, Mean (????̅) = 67.69, Median = 68.00, Variance = 92.961 and standard deviation = 9.642. Based on the data above, it can be said that learning media in the form of the Canva application is considered good, while learning media in the form of the PixelLab application is considered adequate. From the results of the data above, it can be concluded that there is a positive influence of the use of learning media in the form of the Canva application on the ability to write anecdotal texts in class X SMA Negeri 1 Malingping students.